2022
DOI: 10.1126/science.abg6621
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal GPCR-like protein LYCHOS signals cholesterol sufficiency to mTORC1

Abstract: Lysosomes coordinate cellular metabolism and growth upon sensing of essential nutrients, including cholesterol. Through bioinformatic analysis of lysosomal proteomes, we identified LYsosomal CHOlesterol Signaling (LYCHOS, previously annotated as G-protein coupled receptor 155), a multidomain transmembrane protein that enables cholesterol-dependent activation of the master growth regulator, the protein kinase mechanistic Target of Rapamycin Complex 1 (mTORC1). Cholesterol bound to the N-terminal permease-like r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 65 publications
(98 reference statements)
1
28
0
Order By: Relevance
“…3D ). Indeed, prior work has determined that cholesterol directly activates mTORC1 (Castellano et al, 2017; Davis et al, 2021; Lim et al, 2019; Shin et al, 2022). Consistent with our proteomics data, we found that gene sets related to cholesterol synthesis were increased in both cell lines with p16 knock-down and patients with low CDKN2A expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3D ). Indeed, prior work has determined that cholesterol directly activates mTORC1 (Castellano et al, 2017; Davis et al, 2021; Lim et al, 2019; Shin et al, 2022). Consistent with our proteomics data, we found that gene sets related to cholesterol synthesis were increased in both cell lines with p16 knock-down and patients with low CDKN2A expression ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The de novo synthesis pathway is a multi-step process starting with acetyl-CoA and progressing through the mevalonate pathway including conversion of HMG-CoA to mevalonate by the rate limiting enzyme HMG-CoA reductase and then cholesterol synthesis via squalene and lanosterol leading to cholesterol (Shi et al, 2022). Prior work has shown that cholesterol directly activates mTORC1 via LYCHOS at lysosomes (Castellano et al, 2017; Davis et al, 2021; Lim et al, 2019; Shin et al, 2022). Cholesterol has also been linked to genome instability, yet it has been placed upstream of DNA damage accumulation (Liu et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, our data show that the addition of exogenous cholesterol rescues both cell viability and the degradative capacities of lysosomes in MALT-on cells. Whether MALT1 operates upstream of the lysosomal cholesterol-sensing machinery remains to be explored [29][30][31]36 . Moreover, the fact that tumor cells relying on MALT1 activity for their survival 53,68,69,79,80 exhibits selective sensitivity to NPC1 inhibition raises the possibility that the paracaspase might coordinate the overall organization of the lysosomal compartment toward cholesterol handling.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, lysosomes have been attributed crucial roles in nutrient and lipid sensing, and therefore metabolism 28 . Several proteins acting as sensors, including NPC1, LYCHOS, and SLC38A9, were described to gauge cholesterol levels in lysosomes and further transmit the information to the cell [29][30][31] . In this context, the serine/threonine kinase mTOR plays a pivotal role.…”
Section: Introductionmentioning
confidence: 99%
“…In the nutrient signalling area, it remains unclear what are the physiological stimuli for GATOR1 to transition from its inhibitory binding state to its GAP active binding mode. In an exciting advance, cholesterol binding to the lysosomal membrane protein LYCHOS was shown to modulate GATOR1 activity [68]. Further understanding will likely require consideration of the roles of the GATOR2 and KICSTOR complexes, whose functions are still murky.…”
Section: Discussionmentioning
confidence: 99%